The Role of Green Finance in Achieving Sustainable Development Goals: Opportunities and Challenges - Septiani, Novita; Oktavia, Yosi (Civil and Military Cooperation Journal, 2025)
Green finance plays a crucial role in achieving the Sustainable Development Goals (SDGs) by mobilizing financial resources for environmentally sustainable projects. This study explores the opportunities and challenges of green finance in promoting a low-carbon economy while addressing global environmental concerns. It examines various green financial instruments, such as green bonds, sustainable investment funds, and environmentally responsible banking practices. The research highlights the potential of green finance to drive economic growth while ensuring environmental sustainability. However, challenges such as regulatory gaps, financial risks, and market uncertainties hinder its full implementation. By analyzing the link between green finance and SDGs, this study provides insights into how financial systems can support sustainable development and climate resilience.